2004
DOI: 10.1172/jci200421946
|View full text |Cite
|
Sign up to set email alerts
|

Mouse retrovirus mediates porcine endogenous retrovirus transmission into human cells in long-term human-porcine chimeric mice

Abstract: Porcine endogenous retrovirus (PERV) is a potential pathogen in clinical xenotransplantation; transmission of PERV in vivo has been suggested in murine xenotransplantation models. We analyzed the transmission of PERV to human cells in vivo using a model in which immunodeficient NOD/SCID transgenic mice were transplanted with porcine and human lymphohematopoietic tissues. Our results demonstrate, we believe for the first time, that human and pig cells can coexist long-term (up to 25 weeks) without direct PERV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Despite this lack of tropism, PERV sequences were found in human cells. This transmission was the result of pseudotyping of PERV-C by murine leukemia virus, a feature that exaggerated the infectivity of PERV for human cells [29 ]. This observation was confirmed in a series of experiments including human-tropic PERV-A and PERV-B [30 ].…”
Section: Pseudotypingmentioning
confidence: 70%
“…Despite this lack of tropism, PERV sequences were found in human cells. This transmission was the result of pseudotyping of PERV-C by murine leukemia virus, a feature that exaggerated the infectivity of PERV for human cells [29 ]. This observation was confirmed in a series of experiments including human-tropic PERV-A and PERV-B [30 ].…”
Section: Pseudotypingmentioning
confidence: 70%
“…Although PERV DNA and PERV env RNA sequences were consistently identified in the intact xenografts, indicating persistent intragraft transcription of PERV sequences and possibly PERV replication, no PERV transmission to host mouse tissues was demonstrated. Other groups have reported a low incidence of PERV transmission to host mouse tissues after transplantation of pig islet tissue 15 , 16 , 32 but independent studies have suggested that this may be due to pseudotyping of PERV by xenotropic murine leukemia virus 33 , 34 because mice lack the appropriate PERV receptor 22 . Although fetal lamb tissues can express ovine endogenous retrovirus (OERV) transcripts, the production and release of endogenous retrovirus by fetal lamb cells is unclear and virions have not been reported 35 .…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that in the case of clinical xenotransplantation, heavy immunosuppression of transplant recipients may facilitate intragraft PERV replication, pig cell microchimerism and PERV transmission to host tissues. In view of host range restrictions, however, receptor‐mediated cell entry 40 into novel hosts, such as humans, may require recombination between different PERV subclasses 41 and/or pseudotyping with host endogenous retrovirus(es) 33 , 34 . Both cell entry and integration of PERV sequences into the host genome therefore represent vital targets for intercepting PERV transmission 40 , 42 , 43 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is still unknown whether murine endogenous viruses influence PERV infection in this model. When the adequacy of the models is evaluated, it is still debatable whether PERV can be transmitted by themselves or whether they must be pseudotyped by xenotropic endogenous retroviruses of the host species (Yang et al, 2004), which makes the model under consideration inapplicable to human xenotransplantation, because these viruses can be absent in the DNA of human germinal cells.…”
Section: Studying Of Perv Transmissionmentioning
confidence: 99%